Implementation of the Analytical Hierarchy Process Method as a Media for Decision Making on the Admission of Candidates for the Kalirejo Village, Central Lampung - Donny Muda Priyangan; Hara Fransiska (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2020)
Development, intelligent and competent village officials are people who are strong in facing changes in village institutions, not only driven by internal factors but also external factors. Internal factors because when the Village Apparatus must have certain skills and knowledge such as making village regulations with the consultative body, managing village finances, and others. The village community's demand for satisfactory services is something that the village government must immediately respond to. The results that can be concluded from this study are that the performance of the village government in providing services must be maximized, for the creation of good government. A decision support system is generally defined as a system that is capable of producing solutions and handling problems. Decision support systems are not intended to replace the role of decision-makers, but to assist and support decision-makers. So it is necessary to make a Decision Support System by applying the Analytical Hierarchy Process (AHP) method. The AHP method is a method used to assess actions that are associated with a comparison of the weights of importance between factors and a comparison of several alternative choices. This method will give the results of the weighting of each alternative choice in accordance with many established criteria.